PERAN MAGIS-RELIGIUS BENGAWAN SOLO DALAM PENDIRIAN KOTA SURAKARTA ABAD KE-18 - Mimi Savitri (KALPATARU, 2015)
The magical-religious role of Bengawan Solo (Solo River) in the establishment of Surakarta was crucial. It was related to mystical power, ghosts, or spirits of ancestors, especially those that reside at a confluence of two rivers. Belief in mystical power was the foundation of Javanese life, but not enough attention has been paid by historians as well as archaeologists. The aim of this research is to widen people’s insight about the belief of the Javanese people to the supernatural power and spirits that inhabited their dwelling places. Survey, phenomenology, and bibliographical study are the methods used to reveal more about the magical-religious role of the river. Results of the research are an understanding of the magical-religious role of Bengawan Solo in the establishment of Surakarta city as shown in the location of the city, which is close to the confluence of two rivers because such location is conceived as sacred, and the other is a belief to the Javanese cosmological concept that rivers are important to the establishment of city layout. It also proves that there is a continuity among the Javanese people who live around the Bengawan Solo from the past until nowadays. Peran magis religius Bengawan Solo adalah penting bagi pendirian Kota Surakarta. Peran ini berkaitan dengan kekuatan gaib, roh halus, dan atau roh-roh nenek moyang yang ada pada sungai khususnya di daerah pertemuan dua sungai. Kepercayaan terhadap kekuatan gaib merupakan hal mendasar dalam kehidupan orang Jawa, akan tetapi hal tersebut kurang mendapat perhatian dari para ahli sejarah maupun arkeologi. Tujuan dari penelitian ini adalah untuk memperluas wawasan mengenai kepercayaan orang Jawa terhadap kekuatan gaib dan roh halus yang ada pada tempat tinggal mereka. Survei, fenomenologi, dan kajian pustaka adalah metode yang digunakan untuk mengungkap lebih dalam peran magis religius dari sungai tersebut. Hasil dari penelitian ini adalah peran magis religius Bengawan Solo terhadap Kota Surakarta, yaitu daerah sekitar pertemuan dua sungai karena dianggap sakral dan kepercayaan terhadap konsep kosmologi Jawa, bahwa sungai merupakan bagian penting dalam pembentukan tata ruang kota. Penelitian ini sekaligus membuktikan adanya kontinuitas budaya yang hidup di masyarakat sekitar Bengawan Solo sejak dahulu hingga kini.